2016
DOI: 10.1016/j.biopsycho.2016.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Do depressive symptoms “blunt” effort? An analysis of cardiac engagement and withdrawal for an increasingly difficult task

Abstract: Research on depression and effort has suggested “depressive blunting”—lower cardiovascular reactivity in response to challenges and stressors. Many studies, however, find null effects or higher reactivity. The present research draws upon motivational intensity theory, a broad model of effort that predicts cases in which depressive symptoms should increase or decrease effort. Because depressive symptoms can influence task-difficulty appraisals—people see tasks as subjectively harder—people high in depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Furthermore, “unattainability” is in the eye of the beholder, and while some people may be reluctant to accept that a goal is unattainable, others (ie, those with depression) may be much too quick to do so. Researchers have suggested that disengagement in the context of clinical depression may be maladaptive and reflect goal abandonment or premature “giving up.” This notion is consistent with prior research showing that depressed individuals disengage more quickly from difficult tasks and fail to appropriately calibrate mobilization of effort according to task difficulty …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, “unattainability” is in the eye of the beholder, and while some people may be reluctant to accept that a goal is unattainable, others (ie, those with depression) may be much too quick to do so. Researchers have suggested that disengagement in the context of clinical depression may be maladaptive and reflect goal abandonment or premature “giving up.” This notion is consistent with prior research showing that depressed individuals disengage more quickly from difficult tasks and fail to appropriately calibrate mobilization of effort according to task difficulty …”
Section: Discussionsupporting
confidence: 89%
“…35 This notion is consistent with prior research showing that depressed individuals disengage more quickly from difficult tasks 36 and fail to appropriately calibrate mobilization of effort according to task difficulty. 37 Thus, researchers have suggested that successful goal adjustment, in the face of unattainable goals, also requires goal reengagement. 20,21 Specifically, individuals who are able to reengage in new goals experience more positive emotions 27,38 and fewer depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that individual differences in perfectionism predict effort measured by self-reported effort and time spent practicing [ 12 , 14 , 15 ]. However, within the current study, perfectionism did not predict effort in a paradigm that has been effective in examining whether individual-differences predict effort (i.e., grit, self-focused attention, and anhedonic depression; [ 25 , 36 , 43 ]). Moving forward with research on perfectionism and motivation, it will be important to use physiological measures of effort in addition to self-report and performance measures because these indicators of effort commonly diverge.…”
Section: Discussionmentioning
confidence: 61%
“…For each physiological outcome, scores for the 5 baseline minutes were averaged to form a baseline value, and scores for the 3 parity task minutes were averaged to form a task value. We analyzed the data using regression models, as in our recent work [ 43 , 44 ]. Reactivity scores—change from baseline to task—were computed by subtracting the baseline value from the task value.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, Experiment 2 indicates that prioritizing benefit over cost information influences preference and decision. Recent research showed altered effort-based decision-making in patients with depression (Silvia et al, 2016;Treadway, Bossaller, Shelton, & Zald, 2012;Yang et al, 2014), schizophrenia (Barch, Treadway, & Schoen, 2014;Culbreth, Westbrook, & Barch, 2016;McCarthy, Treadway, Bennett, & Blanchard, 2016), and bipolar disorder (Hershenberg et al, 2016). Generally, these populations tend either to avoid more effortful tasks or to show inefficient effort allocation.…”
Section: Discussionmentioning
confidence: 99%